Interaction between the hypothalamo-pituitary-adrenal and thyroid axes during immobilization stress - Kadhim, Hakeem J.; Kuenzel, Wayne J. (Frontiers in Physiology, 2022)
The location of corticotropin-releasing hormone receptor 2 (CRH-R2) on thyrotropes within the avian anterior pituitary (APit) and its activation by different stressors indicate a possible communication between hypothalamo-pituitary-adrenal (HPA) and thyroid (HPT) axes. Therefore, an experiment was designed to 1) compare the timing of major components of the HPT axis to those of the HPA axis; 2) address whether stressors activating the HPA axis may simultaneously upregulate components of the HPT axis. Blood, brain, and APit were sampled from chicks prior to stress (control) and 15, 30, 60, 90, and 120 min following immobilization (IM) stress. The nucleus of the hippocampal commissure (NHpC) and paraventricular nucleus (PVN) were cryo-dissected from brains for RT-qPCR. Gene expression of thyrotropin-releasing hormone (TRH) and its receptors (TRH-R1 and TRH-R3), urocortin3 (UCN3), deiodinase 2 (D2), and the second type of corticotropin-releasing hormone (CRH2) within the NHpC and PVN was measured. Additionally, gene expression of TRH receptors, thyroid stimulating hormone subunit beta (TSHβ), and D2 was determined in the APit and corticosterone assayed in blood. In brains, a significant upregulation in examined genes occurred at different times of IM. Specifically, UCN3 and CRH2 which have a high affinity to CRH-R2 showed a rapid increase in their mRNA levels that were accompanied by an early upregulation of TRHR1 in the NHpC. In the APit, a significant increase in gene expression of TSHβ and TRH receptors was observed. Therefore, results supported concurrent activation of major brain and APit genes associated with the HPA and HPT axes following IM. The initial neural gene expression originating within the NHpC resulted in the increase of TSHβ mRNA in the APit. Specifically, the rapid upregulation of UCN3 in the NHpC appeared responsible for the early activation of TSHβ in the APit. While sustaining TSHβ activation appeared to be due to both CRH2 and TRH. Therefore, data indicate that CRH-producing neurons and corticotropes as well as CRH- and TRH-producing neurons and thyrotropes are activated to produce the necessary energy required to maintain homeostasis in birds undergoing stress. Overall, data support the inclusion of the NHpC in the classical avian HPA axis and for the first time show the concurrent activation of the HPA axis and components of the HPT axis following a psychogenic stressor.